2016
DOI: 10.2105/ajph.2016.303372
|View full text |Cite
|
Sign up to set email alerts
|

Replicating the Safer Sex Intervention: 9-Month Impact Findings of a Randomized Controlled Trial

Abstract: SSI produced meaningful changes in sexual behavior and sexual risk and successfully addressed some potential antecedents of sexual risk behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…It consisted of one initial session lasting 30-50 min and three booster sessions delivered at one, three, and 6 months. A randomized controlled trial comparing intervention groups from 2012 to 2015 described an overall significant increase of condom use at 9 months, as well as behavioural changes for Hispanic youth [33]. The main difference between this intervention and the SIRIAN program is the community dimension of the latter, which increases the access of newcomers and populations vulnerable to healthcare, without replacing it.…”
Section: Discussionmentioning
confidence: 99%
“…It consisted of one initial session lasting 30-50 min and three booster sessions delivered at one, three, and 6 months. A randomized controlled trial comparing intervention groups from 2012 to 2015 described an overall significant increase of condom use at 9 months, as well as behavioural changes for Hispanic youth [33]. The main difference between this intervention and the SIRIAN program is the community dimension of the latter, which increases the access of newcomers and populations vulnerable to healthcare, without replacing it.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis consisting of 60 studies examining the impact of school-based comprehensive sex education, Weed and Ericksen [31] found that CSE was not effective to decrease teen pregnancy as well as STD rates and to increase abstinence and condom use at 12-months post-program [16]. Several studies were identified to have yielded negative effects including higher levels of sexual initiation, oral sex, and reduced contraceptive use [44,45]. On the other hand, some school-based abstinence education programs revealed sustained increases in teen abstinence.…”
Section: Sex Education In the United States Of Americamentioning
confidence: 99%
“…Of the 40 studies, 14 were NRSIs,25–38 11 were RCTs39–49 and 15 were cRCTs 50–64. Some 29 studies targeted adolescents26 27 29 30 32 35–37 40–42 44–48 50–53 55 57–64 and 11 targeted adolescents and young adults 25 28 31 33 34 38 39 43 49 54 56.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 40 studies, 14 were NRSIs,25–38 11 were RCTs39–49 and 15 were cRCTs 50–64. Some 29 studies targeted adolescents26 27 29 30 32 35–37 40–42 44–48 50–53 55 57–64 and 11 targeted adolescents and young adults 25 28 31 33 34 38 39 43 49 54 56. Of all the studies, 32 targeted both genders25–35 37 40–42 44 46 47 50–62 64 and 8 included females only 36 38 39 43 45 48 49 63.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation